Bending-durable membrane-electrode assembly using metal nanowires for bendable polymer electrolyte membrane fuel cell - Kang, Yun Sik; Won, Phillip; Ko, Seung Hwan; Park, Taehyun; Yoo, Sung Jong (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
We herein report a simple and effective strategy to fabricate the bending-durable membrane-electrode assembly for bendable polymer electrolyte membrane fuel cells (PEMFCs) by simply coating conventional carbon papers with manually fabricated silver nanowires (Ag NWs). Due to the high stretchability and flexibility of Ag NWs, we expect that the introduction of Ag NWs to carbon fibers would relieve the increase of ohmic and charge transfer resistances derived from the disconnections between each carbon fiber and the resulting decrease of electrical conductivity by repeatedly bending the bendable PEMFCs. We find that by using Ag NWs as an added component to carbon paper, the performance of Ag NWs-applied PEMFC can be maintained after repetitive bending. Carbon papers with the Ag NWs also show higher performance than the PEMFC without Ag NWs in the previous research. From the electrochemical impedance spectra of Ag NWs-coated PEMFC, it is clearly demonstrated that the coated Ag NWs effectively connect between carbon fibers and thereby play a role as a good buffer medium when carbon fibers are disconnected by mechanical bending. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: PERFORMANCE VARIATION; CURRENT COLLECTOR; TECHNOLOGY; BATTERIES